Moving Next-Generation Sequencing into the Clinic - Shetty, Omshree; Gurav, Mamta; Bapat, Prachi; Karnik, Nupur; Wagh, Gauri; Pai, Trupti; Epari, Sridhar; Desai, Sangeeta (Indian Journal of Medical and Paediatric Oncology, 2021)
With an advancement in the field of molecular diagnostics, there has been a profound evolution in the testing modalities, especially in the field of oncology. In the past decade, sequencing technology has evolved drastically with the advent of high-throughput next-generation sequencing (NGS). Subsequently, the single-gene tests have been replaced by multigene panel-based assays, deep sequencing, massively parallel whole genome, whole-exome sequencing, and so on. NGS has provided molecular diagnostics professionals a wonderful tool to explore and unearth the genetic alterations, underpinning the pathophysiology of the disease. However, this development has posed new challenges which consist of the following; understanding the technology, types of platforms available, various sequencing strategies, bioinformatics and data analysis algorithm, reporting of various variants, and validation of assays and overall for developing NGS assay for clinical utility. The challenges involved sometimes impede development of these high-end assays in laboratories. The present article provides a broad overview of our journey in setting up the NGS assay in a molecular pathology laboratory at a tertiary care oncology center. We hereby describe various important points and steps to be followed while working on the NGS setup, right from its inception to final drafting of the reports, with inclusion of various validation steps. We aim at providing a beginner’s guide to set up NGS assays in the laboratory using recommended best practices and various international guidelines.
Keywords: molecular diagnostics; NGS; oncology